Exploring Variability of Trichodesmium Photophysiology Using Multi-Excitation Wavelength Fast Repetition Rate Fluorometry - Zhu, Yuanli; Feng, Yuanyuan; Browning, Thomas J.; Wen, Zuozhu; Hughes, David J.; Hao, Qiang; Zhang, Ruifeng; Meng, Qicheng; Wells, Mark L.; Jiang, Zhibing; Dissanayake, P. A. K. N.; Priyadarshani, W. N. C.; et al. (Frontiers in Microbiology, 2022)
Fast repetition rate fluorometry (FRRf) allows for rapid non-destructive assessment of phytoplankton photophysiology in situ yet has rarely been applied to Trichodesmium. This gap reflects long-standing concerns that Trichodesmium (and other cyanobacteria) contain pigments that are less effective at absorbing blue light which is often used as the sole excitation source in FRR fluorometers—potentially leading to underestimation of key fluorescence parameters. In this study, we use a multi-excitation FRR fluorometer (equipped with blue, green, and orange LEDs) to investigate photophysiological variability in Trichodesmium assemblages from two sites. Using a multi-LED measurement protocol (447+519+634 nm combined), we assessed maximum photochemical efficiency (Fv/Fm), functional absorption cross section of PSII (σPSII), and electron transport rates (ETRs) for Trichodesmium assemblages in both the Northwest Pacific (NWP) and North Indian Ocean in the vicinity of Sri Lanka (NIO-SL). Evaluating fluorometer performance, we showed that use of a multi-LED measuring protocol yields a significant increase of Fv/Fm for Trichodesmium compared to blue-only excitation. We found distinct photophysiological differences for Trichodesmium at both locations with higher average Fv/Fm as well as lower σPSII and non-photochemical quenching (NPQNSV) observed in the NWP compared to the NIO-SL (Kruskal–Wallis t-test df = 1, p < 0.05). Fluorescence light response curves (FLCs) further revealed differences in ETR response with a lower initial slope (αETR) and higher maximum electron turnover rate (ETRPSIImax) observed for Trichodesmium in the NWP compared to the NIO-SL, translating to a higher averaged light saturation EK (= ETRPSIImax/αETR) for cells at this location. Spatial variations in physiological parameters were both observed between and within regions, likely linked to nutrient supply and physiological stress. Finally, we applied an algorithm to estimate primary productivity of Trichodesmium using FRRf-derived fluorescence parameters, yielding an estimated carbon-fixation rate ranging from 7.8 to 21.1 mgC mg Chl-a–1 h–1 across this dataset. Overall, our findings demonstrate that capacity of multi-excitation FRRf to advance the application of Chl-a fluorescence techniques in phytoplankton assemblages dominated by cyanobacteria and reveals novel insight into environmental regulation of photoacclimation in natural Trichodesmium populations.